SCANNING ELECTRON MICROSCOPY - A GOOD CHOICE FOR STUDY DENTAL HARD TISSUE AND BIOMATERIAL STRUCTURE - Ion Hurjui; Cristian Statescu; Carina Balcos; Ion Andrei Hurjui; Ruxandra Maria Hartan; Maria-Alexandra Martu; Carmen Delianu; Iulia Cătălina Săveanu; Ionela Lacramioara Serban (Romanian Society of Oral Rehabilitation, 2021)
In restorative dentistry, in situ replication of intra-oral situations is based on a method of evaluating non-invasive and non-destructive scanning electron microscopy (SEM). SEM is one of the electron microscope technique that produces images of a sample by scanning the surface with a focused beam of electrons. The technique has multiple indicationsand also is suitable for investigating restorative materials, dental hard and soft tissues and their interfaces. Biomaterials are now widespread in general, either for therapeutic purposes or in the supply of missing biological structures. The environment of the oral cavity into which biomaterials are introduced is very complex. It can be variable depending on the salivary pH but also depending on the general pathology and the medication administered to the respective patients. Since its inception and introduction in dental research electron microscopy has a wide range of applications involving dental biomaterials.